Third-generation laser balloon ablation for atrial fibrillation treatment: a multicenter experience. (14th October 2021) - Rovaris, G; Martignani, C; Miracapillo, G; Colella, A; Giaccardi, M; Forleo, G.B; Giomi, A; Giacopelli, D; Grassini, D; Pozzi, M; Montemerlo, E; Ziacchi, M; et al.
Abstract: Background: Laser balloon ablation is a promising option for performing pulmonary vein isolation (PVI) which is the cornerstone of invasive atrial fibrillation (AF) treatment. Purpose: We aimed to investigate the acute efficacy and safety of the novel third-generation of the laser balloon system in an initial multicenter experience. Methods: First and consecutive patients who underwent PVI with LB3 for drug-resistant paroxysmal or persistent AF at 7 Italian sites were included in this analysis. Study endpoints were acute procedural efficacy, defined as successful isolation of all identified PVs without radiofrequency touch-up, total and fluoroscopy times, and periprocedural complications. Results: Our population included 86 patients (81% males, mean age 60.6±9.5 years) who underwent a procedure of PVI using LB3 between June 2020 and March 2021. Most patients had paroxysmal AF (74%) and were in sinus rhythm at the beginning of the procedure. The mean procedure time was 138±60 min; fluoroscopy time was 22±17 min and the mean ablation time was 44±40 min. Of the 313 targeted PVs, 311 (99.4%) could be isolated with first-pass LB3 application, while 2 (0.6%) required radiofrequency touchup. At the end of the procedure, all patients were in sinus rhythm and 26 (32%) received electrical cardioversion to achieve stable sinus rhythm. The total rate of major compilations was 1.2% (1/82 patients): one pericardial tamponade requiring epicardial puncture. No surgical intervention was necessary, and the patient recovered without any sequalae. There were no vascular access complications or phrenic nervy palsy. Three pinhole balloon raptures (3.5%) were observed during energy applications that required replacement of the whole system but had no effect on patient safety. Conclusions: In a first multicenter experience, the LB3 system for PVI was safe with excellent acute efficacy. Funding Acknowledgement: Type of funding sources: None.